A HUBUNGAN ANTARA TINGKAT PENGETAHUAN DAN SANITASI LINGKUNGAN TERHADAP KEJADIAN DIARE PADA BALITA DI PUSKESMAS SAWIT SEBERANG LANGKAT SUMATERA UTARA 2023-2024: HUBUNGAN ANTARA TINGKAT PENGETAHUAN DAN SANITASI LINGKUNGAN TERHADAP KEJADIAN DIARE PADA BALITA DI PUSKESMAS SAWIT SEBERANG LANGKAT SUMATERA UTARA 2023-2024 - Christina Leony Sinaga; Surjadi Rimbun; Menang Bastanta Tarigan; Eka Samuel Parulian Hutasoit; Jadeny Sinatra (Jurnal Kedokteran Methodist, 2024)
ABSTRACT Diarrhea remains a global health issue, including in Indonesia. According to the 2020 Indonesian nutrition status survey, the prevalence of diarrhea was recorded at 9.8%. Various factors influence the occurrence of diarrhea in toddlers, with mothers playing a crucial role in prevention and treatment. Mothers with knowledge of the causes, symptoms, and prevention of diarrhea are key in maintaining hygiene and preventing disease. The mother's education level also plays a significant role, as higher-educated mothers tend to more easily receive information and apply preventive measures. With adequate knowledge, mothers can be more careful in caring for their children, from providing clean water to managing waste, thereby reducing the incidence of diarrhea in toddlers. Conclusion: there is a significant relationship between the mother's knowledge and environmental sanitation quality with the incidence of diarrhea in toddlers at Puskesmas Sawit Sebrang, Langkat, North Sumatra..